Old-Age home?: middle-class senior citizens and new elderscapes in urban India - Mayer, Annika (2017)
The ethnographic study pursues the question how recent social and urban transformations in India have altered ways of ageing. The focus lies on changes people experience and create. Mayer looks at the dynamic interplay of larger transformations – India’s shift to a neoliberal economy, the increase of migration and urbanisation – and smaller transitions in individual life courses to come to a better understanding of how to conceptualise ageing in times of globalisation.
Keywords: Leibniz-Institut für Arbeitsforschung an der TU Dortmund -- Arbeitsgruppe Altern und ZNS-Veränderungen; Indien; Hochschulschrift